PENERAPAN METODE BERMAIN PERAN DALAM MENGEMBANGKAN SIKAP SOSIAL ANAK USIA DINI DI TK ISLAM DARUL ULUM TANJUNG HERAN KECAMATAN PUGUNG TAHUN PELAJARAN 2023/2024 - Eli Nurmayanti (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
The population in this study were students at the Darul Ulum Islamic Kindergarten in Tanjung Heran, Pugung District, consisting of classes A, B and C. Therefore, the researcher wanted to try to reveal how to implement experimental methods to develop simple science skills in kindergarten children. in overcoming students’ difficulties and mistakes. Seeing the above phenomenon, the researcher was interested in researching the existence of this school, namely the Darul Ulum Tanjung Heran Islamic Kindergarten, Pugung District. The aim of this researcher is to describe the efforts of fiqh teachers in overcoming difficulties. Darul Ulum Islamic Kindergarten, Tanjung Heran, Pugung District with all its supporting and inhibiting factors. To obtain data in the research the author used descriptive qualitative research methods, the data was produced through observation, interview and documentary methods. The conclusion drawn from the research results is: Application of the Role Playing Method in Developing Social Attitudes of Darul Ulum Islamic Kindergarten students in Tanjung Heran, Pugung District, choosing a practical method, the teacher practices the way of praying and the students follow it. The suggestions in this research for teachers are: A teacher who teaches should be professional in their field and have shown good results.